A New Species of Simulium (simulium) (diptera: Simuliidae) from Langkawi Island, Peninsular Malaysia - Takaoka, H.; Sofian-Azirun, Mohd; Ya'cob, Z. (2012)
Simulium (Simulium) kisapense sp. nov. is described on the basis of reared adult, pupal, and larval specimens collected from Langkawi Island, Peninsular Malaysia, and placed in the multistriatum species-group in the subgenus Simulium. This new species is characterized by the bare basal section of the female radial vein, the male ventral plate with setae, the eight pupal gill filaments divergent at an angle of >90 degrees, and the shoe-shaped cocoon with small lateral window(s). Taxonomic notes are given to separate this new species from S. (S.) hirtinervis Edwards and S. (S.) malayense Takaoka and Davies, both from Peninsular Malaysia, and several other known species from Bhutan, India, Nepal, and Thailand. Â© 2012 Entomological Society of America.